Efficacy of insecticides and red seaweed extract (Kappaphycus alvarezii) in the management of sesamum phyllody disease - Bharathi K.B.; Prema G.U.; Prakash H.T. (Annals of Agricultural Research, 2024)
Sesamum crop suffers from many diseases caused by fungi, bacteria and phytoplasma. Amongst all the diseases, phyllody is a very serious disease in most sesamum growing regions. Phyllody means transforma tion of floral parts into green leaf like strucutres which is caused by phytoplasma and transmitted by leaf hopper, Orosius albicinctus Distant. For the management of vector of sesamum phyllody, the experiment was conducted during Kharif, 2021 in a Randomised Block Design with eight treatments and three replications at College of Agriculture, Vijayapur. Among the different treatments tested during Kharif 2021, foliar spray of thiamethoxam 25% WG @ 0.2 g/l recorded highest per cent reduction of leaf hopper population over control and also recorded lowest disease incidence starting from vegetative stage to maturity stage with higher seed yield. Thiamethoxam acts by binding to nicotinic acetylcholine receptors. It provides an excellent control for broad range of commercially important sucking pests. Foliar spray of imidacloprid 350 SC (0.3 ml/l) was also found on par with thiamethoxam. Untreated check recorded higher disease incidence and harboured more number of leaf hoppers, recorded low yield when compared to all other treatments